TRP ion channels in thermosensation, thermoregulation and metabolism - Wang, Hong; Siemens, Jan (Temperature, 2015)
In humans, the TRP superfamily of cation channels includes 27 related molecules that respond to a remarkable variety of chemical and physical stimuli. While physiological roles for many TRP channels remain unknown, over the past years several have been shown to function as molecular sensors in organisms ranging from yeast to humans. In particular, TRP channels are now known to constitute important components of sensory systems, where they participate in the detection or transduction of osmotic, mechanical, thermal, or chemosensory stimuli. We here summarize our current understanding of the role individual members of this versatile receptor family play in thermosensation and thermoregulation, and also touch upon their immerging role in metabolic control.
Gesehen am 06.12.2021